In situ preparation of alendronate-loaded ZIF-8 nanoparticles on electrospun nanofibers for accelerating early osteogenesis in osteoporosis. (May 2022) - Al-Baadani, Mohammed A.; Xu, Lihua; Hii Ru Yie, Kendrick; Sun, Anba; Gao, Xue; Cai, Kexin; Al-Shaaobi, Bilal A.; Al-Bishari, Abdullrahman M.; Cai, Lei; Shen, Xinkun; Liu, Jinsong; Ma, Pingping
Graphical abstract: Highlights: Alendronate-loaded zeolitic imidazolate framework-8 nanoparticles are fabricated in situ on polycaprolactone/gelatin blend nanofibers. The target membrane has superior mechanical stability. The alendronate and zeolitic imidazolate framework-8 interaction significantly reduced the release of zinc ion and alendronate. The target membrane shows good bactericidal activity against Staphylococcus aureus and Escherichia coli. The target membrane augments osteogenesis in the osteoporosis microenvironment. Abstract: Applying guided bone regeneration membrane (GBRm) to treat bone defects in osteoporotic patients remains a challenge, as they cannot restore the fundamental balance between osteoblasts and osteoclasts, resulting in the ineffectiveness of osteoporotic bone injury treatment. Herein, a multifunctional polycaprolactone/gelatin (PG)-blended membrane embedded with alendronate-loaded zeolitic imidazolate framework-8 (Aln/Zif-8) nanoparticles was fabricated by electrospun technique and a simple solution-phase synthesis. Surface characterizations confirmed the successful synthesis of PG/Aln-Zif-8 nanofibers endowed with excellent mechanical strength. The release kinetics analysis showed the synergistic effects of the coordination bonds among Aln, zinc ions (Zn 2+ ), and organic ligands played a critical role in regulating the initial burst release and delayed release of Aln and Zn 2+, respectively. The in vitro results of MC3T3-E1 and RAW264.3 cells demonstrated that the PG/Aln-Zif-8 membranes possessed superior anti-osteoporosis and osteoinductive properties. Furthermore, the PG/Aln-Zif-8 samples also exhibited significant bactericidal properties against both Staphylococcus aureus and Escherichia coli . The in vivo results further confirmed that PG/Aln-Zif-8 membranes had superior osteoinduction abilities, contributing to the accelerated osseointegration in the osteoporosis model. Altogether, these new bioinspired surface modifications highlight the promising alternative for fabricating multifunctional MOFs on electrospun membranes to accelerate early osteogenesis in osteoporosis.